Exact solutions of nonlinear Schrodinger's equation with dual power-law nonlinearity by extended trial equation method - Bulut, Hasan; Pandir, Yusuf; Demiray, Seyma Tuluce (Taylor & Francis Ltd, 2014)
In this paper, we acquire the soliton solutions of the nonlinear Schrodinger's equation with dual power-law nonlinearity. Primarily, we use the extended trial equation method to find exact solutions of this equation. Then, we attain some exact solutions including soliton solutions, rational and elliptic function solutions of this equation using the extended trial equation method.
Keywords: Exp-Function Method; Evolution-Equations; Wave Solutions; Soliton